Engineering Properties and Applications of Air-Foamed Lightweight Soil - Xuze Yuan; Zheng Lu; Hailin Yao; Xianjun Tan; Yang Zhao; Chuxuan Tang; Ming Cheng; YiPeng Gao (Advances in Materials Science and Engineering)
With the continuous development of road construction worldwide, the construction sector is trying to find a versatile material for building roads in particular areas. Air-foamed lightweight soil, which is produced using low-cost raw materials and has a lower density varying from 300 to 1800 kg/m3, adjustable strength, excellent thermal isolation, and a more straightforward construction method, has emerged as a worthy candidate. This paper reviews air-foamed lightweight soil in terms of its composition as well as physical and mechanical properties, such as its compressive strength, flexural strength, and stability. This paper also generalizes the engineering applications of air-foamed lightweight soil and provides ideas for its wide use.